Matrix revolutions / dirigida por Andy Wachowski y Larry Wachowski - Wachowski, Larry; Wachowski, Andy; Moss, Carrie-Anne; Fishburne, Laurence; Reeves, Keanu, 1964- (Madrid Warner Bros, 2003)
The human city of Zion defends itself against the massive invasion of the machines as Neo fights to end the war at another front while also opposing the rogue Agent Smith.
Keanu Reeves, Laurence Fishburne, Carrie-Ann Moss
No recomendada para menores de 13 años
Hablado en inglés y castellano, con posibilidad de cambiar de lengua. Subtítulos en inglés, castellano, portugués e inglés para sordos
Keywords: Películas cinematográficas -- DVD